New developments in Islamic economics - Asmak Ab. Rahman (Emerald Publishing Limited, 2018)
New Developments in Islamic Economics: Examples from Southeast Asia investigates the latest developments in a vibrantand fast-moving area of practical financial and economic study. Primarilyfocused on Malaysian contexts, while also presenting perspectives fromIndonesia and Thailand, this book examines the Asian nations leading the worldin the application of Islamic finance.Case studies analyse anddiscuss new and emerging issues in Islamic economics, including microtakaful,waqf, social finance and poverty alleviation from an Islamic perspective.
Prelims -- Part I Social finance -- Entrepreneurship development in Islamic economics -- Application of the concept of Maslahah in household debt management -- Role of Infaq in Financing students in Malaysian public universities -- Part II WAQF -- Cash Waqf from the perspective of Majelis Ulama Indonesia (MUI) and the scholars of Aceh: an analysis -- The potential of Cash Waqf in the socio-economic development of society in Kelantan -- Empowering society through Waqf Bazars: a case study in Kelantan, Malaysia -- Part III Takaful -- Micro-Takaful in Aceh: does society need it? -- Women and risk: does Takaful have the solution? -- The Islamic perspective on the underwriting of health Takaful products: a study of selected Takaful operators in Malaysia -- Society's understanding of family Takaful: a study in Southern Thailand -- Part IV Banking institutions -- The application of Bay' Al-Tawarruq in Islamic banking institutions in Malaysia: a study of bank Muamalat Malaysia Berhad -- Determinants of the asset structure of Malaysian Islamic banks: a panel study -- Islamic versus conventional banking: characteristics and stability analysis of the Malaysian banking sector -- Index.
Includes index.
Print version record
Keywords: Economics -- Islamic countries; Economics -- Southeast Asia; Economics -- Religious aspects -- Islam; Business & Economics, Islamic Banking & Finance; Economic theory & philosophy